INTERACTIVE METHODS USED TO IMPROVE THE EFFECTIVENESS OF ELEMENTARY SCHOOL READING LESSONS - Zokirov, Javohir G‘aybullo o‘g‘li (Educational Research in Universal Sciences, 2024)
Today, we will present our ideas about the methods used to improve the effectiveness of primary school reading classes, advanced pedagogic and new information technologies from the teacher.